2004
DOI: 10.1097/01202412-200409000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Delayed union and non-union of the ulna following intramedullary nailing in children

Abstract: Most studies report little or no problem with union following intramedullary nailing of fractured forearm bones in children. The bone involved in the occasional delayed union is not mentioned except for one delayed union of the ulna following an open fracture. The present paper specifically highlights problems with union of the ulna following nailing in children. It reports two cases of delayed union and one non-union following nailing of closed fractures of both forearm bones. In all cases, the radius united … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 6 publications
1
28
1
2
Order By: Relevance
“…None of our patients had significant medical problems affecting their bones. Ogonda et al [14] also described the potential problems of delayed union and nonunion of the ulna after intramedullary nailing in children. The explanation proposed for ulna nonunion relates to the possibility that antegrade nailing of the ulna may cause some fracture site distraction in the ulna, whereas retrograde nailing of the radius causes fracture compression in the radius.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…None of our patients had significant medical problems affecting their bones. Ogonda et al [14] also described the potential problems of delayed union and nonunion of the ulna after intramedullary nailing in children. The explanation proposed for ulna nonunion relates to the possibility that antegrade nailing of the ulna may cause some fracture site distraction in the ulna, whereas retrograde nailing of the radius causes fracture compression in the radius.…”
Section: Discussionmentioning
confidence: 95%
“…Ogonda et al [14] have reported a case of ulnar nonunion in a 7-year-old boy with Osteogenesis imperfecta after open reduction and intramedullary ulnar fixation with Steinmann pin. None of our patients had significant medical problems affecting their bones.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge and after an extensive literature search, pediatric nonunion after plate osteosynthesis at a metaphyseal level of the forearm has not been described yet. Even in adults, a nonunion after a metaphyseal forearm fracture is seldomly seen due to a good trabecular bone healing and a good nutritional blood supply of the cancellous bone in the metaphysis of the forearm [4,5,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…It is also very important to minimize the periosteal damage during an operation with a plate osteosynthesis, given the fact that a missing periost can lead to an excessive bone growth towards the opposite direction and so leading to a nonunion. It is recommended to remove a plate osteosynthesis of a diaphyseal forearm fracture between 9 and 12 months because of the risk of refracture with an early plate removal [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Ogonda et al described that antegrade nailing of ulna may cause fracture site distraction and thus delay in bone healing. 27 Additionally, injury in the middle third of shaft of ulna is considered critical as regards to the intraosseous circulation and it may compromise bone healing. 28 Prominent implant with skin irritation was noted in three patients.…”
Section: Discussionmentioning
confidence: 99%